2005
DOI: 10.1359/jbmr.2005.20.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization of Cementoblast Progenitor Cells With Bmi-1 and TERT

Abstract: A cementoblast progenitor cell line designated BCPb8 was successfully isolated from dental follicle cells immortalized with Bmi-1 and hTERT. BCPb8 showed the potential to differentiate into cementoblasts on implantation into immunodeficient mice. BCPb8 was confirmed to be the first established cementoblast progenitor cell line and will provide a useful model for investigating cementogenesis. Introduction:The dental follicle is the mesenchymal tissue surrounding the developing tooth germ. During tooth root deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…In the present study, we showed that PLAP-1/asporin expression is markedly enhanced in dental follicle cells of the developing tooth germ. During tooth germ development, progenitor cells present in the dental follicle are believed to play a central role in the formation of periodontal components such as cementum, periodontal ligament, and alveolar bone (25,26). Taken together, PLAP-1/asporin appears to be involved in the formation of periodontal tissues during tooth development.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we showed that PLAP-1/asporin expression is markedly enhanced in dental follicle cells of the developing tooth germ. During tooth germ development, progenitor cells present in the dental follicle are believed to play a central role in the formation of periodontal components such as cementum, periodontal ligament, and alveolar bone (25,26). Taken together, PLAP-1/asporin appears to be involved in the formation of periodontal tissues during tooth development.…”
Section: Discussionmentioning
confidence: 99%
“…The human periodontal ligament contains multipotent stem cells that differentiate into osteoblasts, cementoblasts, and fibroblasts, and these cells could possibly be used to induce periodontal regeneration (Seo et al 2004(Seo et al ,2005. Additionally, the dental follicle has been utilized as a source of undifferentiated cells in in vitro and in vivo studies (Saito et al 2005). Because the dental follicle and periodontal ligament are immunopositive for periostin (Kruzynska-Frejtag et al 2004;Suzuki et al 2004), this protein is often used as a marker of these tissues.…”
mentioning
confidence: 99%
“…These findings suggest that important regulator genes for osteosarcoma growth may be hypermethylated. BMI-1 co-overexpression with other inducers, such as H-RAS, hTERT and p16 INK4a shRNA, resulted in efficient malignant transformation (36,40,41,44). These findings in turn suggest that other factors might be regulated in addition to BMI-1 to suppress osteosarcoma growth.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that overexpression of EZH2 or BMI-1 promotes malignant transformation (21,36,38,(40)(41)(42)(43)(44)(45)(46)(47). In addition, inhibition of EZH2 or BMI-1 inhibits growth of various types of malignancies (38,41,43,45,46).…”
Section: Knock-down Of Overexpressed Ezh2 and Bmi-1 Does Not Prevent mentioning
confidence: 99%